Employment of the Question as a Transition Mechanism from the Existing to the Desired in Rawiya Jarjoura Burbara’s Collection of Short Stories: L? ?Ur?d? ?an ?A?t?da A?laika/ I Don’t Want to Get Used to You* - Baransi, Rima Abu Jaber (International Journal of Language and Literary Studies, 2021)
This study introduces a critical analytical reading of Rawiya Jarjoura Burbara’s collection of short stories, L? ?Ur?d? ?an ?A?t?da A?laika / I Don’t Want to Get Used to You, published in 2020, a year after the outbreak of the Coronavirus in November 2020. The collection consists of 23 narrative texts that are classified into three chapters. The first chapter is called, A?la -al- ?ar?q– M?a al-N?s/ On the Road-With People, which is the largest chapter and includes 10 short stories; the second chapter is called, A?n al-N?s – Habl al-Kadib/ With People-the Rope of Lies, which consists of 7 short stories, and the third chapter, which is called Ma?ahu-Tuffa?at Adam/ With Him – Adam’s Apple, which consists of 6 short stories. The study attempts to highlight the theme of the ’Question’ in the collection, as the texts, in general, fall in the genre of ’Literature of Question’. Throughout the collection, the writer raises daily life human questions that express her refusal acceptance of matters as they are and getting used to for granted matters as if the possibility of changing them does not exist anymore. The writer introduces questions that are likely to awaken the reader from his hibernation and wake the human beings, in general, to start thinking, questioning, changing, and getting out of the circle of accepting things as for granted and getting used to them. The writer, represented by the Narrators of her stories, refuses to get used to several social, psychological, political, and human life matters.